Rezydencja duchownych w Królestwie Polskim - Jemielity, Witold (Prawo Kanoniczne, 2001)
Church Life in the Congress Kingdom of Poland was subordinated to the Government. As it concerns two periods could be destinguished; till the year 1864 and after the January Uprise. During the first period only the Rector could allow the vicar to leave the parish for a short time, while the Dean could allow both of them to leave the parish for not longer than two weeks. Only the Bishop could allow them to leave the parish for a longer period. After the January Uprise the Rector and the Vicar could move freely only on the area of their own parish, the Dean in his own decanate, while the Bishop in the whole Diocese. Any time they wanted to leave they had to get the permission from the chief of the district or a governor. However, there were special restrictions as concerns going to Warsaw or abroad. Tsar Alexander I on the base of the decree issued on 6 - 18th March 1817 consigned custody and attendance of Roman - Catholic clergymen to one of the state committees. It issued a great mant decrees as concerns the above mentioned subject. The said decrees were sent to parishes sometimes adding their own comments. The Government was more interested in political matters than in those connected with church. It was not as bad as it might have resulted from the civil regulations.